Simulation and design of a wideband T-shaped photonic crystal splitter - Foghani, Shaghayegh; Kaatuzian, Hassan; Danaie, Mohammad (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
In this paper, a high efficiency 2-D T-shaped photonic crystal beam splitter is proposed. It consists of a square lattice of GaAs rods (n = 3.4) embedded in air. The photonic crystal structure proposed can be used for 1550 nm wavelength, which is an important wavelength for optical fiber data transmission. Finite difference time domain (FDTD) simulation results demonstrate that a conventional T-junction can only provide 78% transmission coefficient (39% for each branch) for the incident light, while the proposed T-shaped splitter transmits over 90% of the incident light beam (over 45% from each branch) in the single mode region of waveguide. Especially it transmits nearly 98% (49% from each branch) of the input light in the wavelength of 1550 nm. In other words, the proposed devise shows higher beam splitting efficiency and a wider range of flatness of transmission power spectrum in comparison with previous works.
Optica Applicata, Vol. 40, 2010, nr 4, s. 863-872
Keywords: optyka; photonic crystal; photonic band gap; beam splitter; T-junction; finite difference time domain (FDTD)